Brachioradial pruritus - Descriptive analysis of Brazilian case series - Masuda, Paula Y.; Martelli, Antonio Carlos Ceribelli; Wachholz, Patrick A. [UNESP]; Akumatsu, Hélcio T.; Martins, Ana L. G. P.; Silva, Nathália M. (Wiley, 2013)
Background The epidemiology and clinical features of brachioradial pruritus are variably described in the literature. We sought to analyze these features in a large group of Brazilian patients. Patients and Methods In a descriptive, observational study, we identified all patients with a final diagnosis of brachioradial pruritus seen over a one-year period and re-trospectively reviewed their records. The diagnosis was made after clinical-laboratory investigation had ruled out other causes of chronic pruritus. Demographic and clinical variables were collected along with pruritus characteristics, and analyzed using des-criptive statistics. Results Forty-three patients were identified; their mean age was 55.9 years, with predominance of women (81.4%) and Caucasians (86%). In 52%, the pruritus worsened with heat and sun exposure; 58.1% had intermittent complaints; the ice-pack sign was present only in 20.9%. The arms involving dermatomes C5-C6-C7-C8 (62.8%) were the most affected sites, while psychoactive drugs were the most frequently prescribed therapy. Conclusions Although uncommon, brachioradial pruritus should not be neglected in dermatological diagnosis. This case series analysis indicated that Brazilian patients from a tropical climate show characteristics similar to those described in other series from more temperate regions. © Blackwell Verlag GmbH, Berlin.
Keywords: amitriptyline; betamethasone; carbamazepine; cetirizine; chlorpromazine; citalopram; clobetasol; doxepin; fluoxetine; gabapentin; hydroxyzine; ice; loratadine; pimozide; risperidone; adult; aged; brachioradial pruritus; Brazil; clinical article; clinical feature; cold treatment; comorbidity; dermatome; female; heat; human; lotion; male; prescription; pruritus; race difference; sex difference; sun exposure; treatment response